FEMALE WORKERS IN BANJAR SOCIETY: DYNAMICS, CHALLENGES, AND ECONOMIC CONTRIBUTIONS IN SOUTHERN KALIMANTAN - Sholihin, Rahmat; Rahmaniah , Amelia (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2020)
This study explores the resilience of female workers in Banjar society in South Kalimantan, particularly in three key regions: Banjarmasin, Martapura, and Bati-bati. In Banjar society, working women play a crucial role in supporting both family and community economies. This study highlights the various challenges and opportunities faced by female workers, including online motorcycle taxi drivers (ojol), traditional food vendors, and agricultural laborers. Using a qualitative approach, the study finds that the primary motivation for Banjar women to work is to support their families economically, avoid financial dependency, and maintain social dignity. Despite facing numerous challenges such as harsh working conditions and social stigma, Banjar women persist with resilience and family support. The findings indicate that women’s work in Banjar society is not merely an economic activity but also a vital aspect of social and cultural resilience.